LANGUAGE POLICE BASED ON MINANGKABAU LOCAL WISDOM THROUGH THE VALUES OF DELIBERATION IN BATIKAM STONE FOOTPRINTS AS A GUIDELINE FOR ELEMENTARY SCHOOL STUDENTS - Wirnita Wirnita; Heri Effendi; Erwinsyah Satria; Daswarman Daswarman; Mogastra Rahmana Nursi (Study program PGSD FKIP Universitas Bung Hatta, 2026)
Language politeness is an important part in character building of students since elementary school level.The development of information technology and changes in communication patterns have caused a decline in the quality of language politeness in children, so that learning resources rooted in local culture are needed.This is based on Geoffrey Leech's (1983) theory of politeness.This study aims to describe the level of language politeness based on the local wisdom of Minangkabau traditional leaders through the value of the Jejak Batu Batikam deliberation as a guideline for elementary school students.The study used a quantitative descriptive method.The study population was traditional leaders from the Minangkabau Natural Customary Council (LKAAM) of Tanah Datar Regency.The research sample was 18 traditional leaders selected using a purposive sampling technique.Data were collected through a Likert scale questionnaire containing indicators of language politeness based on the value of the Batu Batikam deliberation.Data analysis used descriptive statistics in the form of averages, percentages, ideal scores, and categories according to Sugiyono.The results showed that the value of language politeness obtained an average of 81.59% with a good category.The dimension of respect for the interlocutor received the highest percentage, at 95.56%, while the dimension of polite criticism received a score of 64.44%.The results indicate that the value of deliberation in Jejak Batu Batikam can be used as a guideline for character education and language politeness in elementary school students.